Battle for Kelantan : will PAS remain in power? - Afif Pasuni (2013)
Kelantan is an opposition-held state where one does not usually expect a fierce electoral battle. But with a small vote swing enough to turn the tide, Kelantan also deserves a closer look during this coming general election.